2001
DOI: 10.1097/00006454-200103000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and immunogenicity of an eleven-valent pneumococcal conjugate vaccine in healthy toddlers

Abstract: An 11-valent mixed carrier pneumococcal conjugate vaccine is safe and immunogenic in toddlers. The use of an adjuvant do not seem to offer any significant benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Priming mice with carrier protein before administration of a conjugate vaccine can either augment or suppress immune response (17); perhaps the latter effect explains the lack of adjuvant effect of alum in our study population. A recent study with children of an 11-valence pneumococcal conjugate vaccine with both diphtheria and TT as carrier proteins also found that alum had no significant effect on immunogenicity (21). Despite the effectiveness of aluminum-based adjuvants in improving immune response to toxoids (6) and the mechanism described to explain its potent effect in vivo (20), little information exists regarding the effect of alum adjuvant on the immunogenicity of conjugate vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Priming mice with carrier protein before administration of a conjugate vaccine can either augment or suppress immune response (17); perhaps the latter effect explains the lack of adjuvant effect of alum in our study population. A recent study with children of an 11-valence pneumococcal conjugate vaccine with both diphtheria and TT as carrier proteins also found that alum had no significant effect on immunogenicity (21). Despite the effectiveness of aluminum-based adjuvants in improving immune response to toxoids (6) and the mechanism described to explain its potent effect in vivo (20), little information exists regarding the effect of alum adjuvant on the immunogenicity of conjugate vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Nieminen et al (13), antibody responses to four 4-valent PCVs were analyzed by non-22F inhibition EIA, and a Ͼ2-fold increase in both anti-PPS IgG and IgM concentrations was detected in at least 25 of 40 children aged 24 months. Also, comparison of the anti-PPS14 IgM concentrations in pre-and postimmunization sera (unpublished data) from a previous study of 11-valent PCV conducted among Israeli toddlers (28) showed low prevaccination anti-PPS14 IgM concentrations and a Ͼ2-fold increase in postvaccination anti-PPS14 IgM concentrations in 15 of 23 toddlers, suggesting vaccine-induced IgM responses (unpublished data).…”
Section: Discussionmentioning
confidence: 90%
“…The remaining four polysaccharides that needed to be administered at higher doses to stimulate immunogenicity were conjugated to DT. The administration of this mixedcarrier conjugate (PncD/T11) simultaneously with a variety of concomitant antigens, including TT and PRP-T to adults, toddlers, and infants, in the presence of wP resulted in a safe and immunogenic formulation (18,21,27,28) (Dagan et al, 37th Annu. IDSA Meet., abstr.…”
Section: Discussionmentioning
confidence: 99%
“…This 11-valent vaccine (PncD/T11) contained seven polysaccharides conjugated to TT and four polysaccharides (those judged to need the largest carrier amounts) conjugated to DT. Initial studies showed it was safe and immunogenic for all 11 pneumococcal serotypes included in the vaccine (serotypes 1, 3, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F) when administered alone or simultaneously with other childhood vaccines, including a combined vaccine consisting of DTwP, PRP-T, and inactivated trivalent poliovirus vaccine (DTwP/IPV/PRP-T) (18,21,27,28;Dagan et al,37th Annu. Infect.…”
mentioning
confidence: 99%